2019
DOI: 10.1155/2019/4230948
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trimetazidine Pretreatment on Endothelial Dysfunction and Myocardial Injury in Unstable Angina Patients Undergoing Percutaneous Coronary Intervention

Abstract: Objectives. Trimetazidine is an anti-ischemic medication licensed for the treatment of angina pectoris. However, the molecular mechanisms underlying its action remain incompletely elucidated. In this study, therefore, we examined the potential beneficial effects of trimetazidine on myocardial injury and endothelial dysfunction in patients with unstable angina in the perioperative period of percutaneous coronary intervention (PCI). Methods. A total of 97 patients with unstable angina were randomly divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…Five studies were then excluded for the following reasons: full-text not available, 20 study results not yet published, 21 patients did not undergo PCI 22 and outcomes not relevant. 23,24 Fifteen trials 10,12,13,15,[25][26][27][28][29][30][31][32][33][34][35] were included in the systematic review and 14 trials in the meta-analysis. Data were not available as mean and standard deviation from one study and hence it was not included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies were then excluded for the following reasons: full-text not available, 20 study results not yet published, 21 patients did not undergo PCI 22 and outcomes not relevant. 23,24 Fifteen trials 10,12,13,15,[25][26][27][28][29][30][31][32][33][34][35] were included in the systematic review and 14 trials in the meta-analysis. Data were not available as mean and standard deviation from one study and hence it was not included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Data of 3 studies 25,26,29 were sourced from a previous meta-analysis. Study participants were described as stable angina patients in 4 studies, 15,27,32,35 unstable angina in 4 trials, 10,12,25,29 acute coronary syndrome in 2 studies 30,33 and acute myocardial infarction (MI) patients in 2 trials. 13,28 Study participants were also diabetic in 2 trials and had chronic kidney disease patients in 1 study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 12 14 ] One study showed that trimetazidine treatment could prevent the increase in creatine kinase-MB, cardiac troponin I, and von Willebrand factor and the decrease in nitric oxide induced by PCI, and improve endothelial dysfunction and myocardial injury. [ 15 ] A meta-analysis showed that additional use of trimetazidine significantly improved the left ventricular ejection fraction and reduced elevated cardiac troponin I level and angina attacks during PCI. [ 16 ]…”
Section: Introductionmentioning
confidence: 99%